Moderating effect of work experience on relationships between predictors and employability among engineering students in Nigerian Polytechnics - Ojonugwa, Oguche Innocent (2015)
Polytechnic is one of the Technical and Vocational Education (TVET) institutions in Nigeria accounting for over 472,000 graduates annually with an annual 20% increase. As the number of Nigerian Polytechnic graduates rise significantly, unemployment rate also increases. The need for polytechnic engineering students to acquire employability skills that will make them marketable and be gainfully employed and fit into the 21st century workforce cannot be over emphasized. In the face of increasing unemployment partly due to decreasing employability skills among Nigeria polytechnic engineering students, many graduates of Nigeria polytechnic have a dwindled confidence of gaining needed employment after graduation. Employability is seen as a construct interrelating to social factors and the individual skills. The study determined the level of employability, basic job performance skills, self-efficacy and subject understanding among engineering students in Nigerian Polytechnics. It further explores the relationship within predictors of employability among engineering students in Nigerian Polytechnics thereby, investigates the dimensionality of the relationships between contributors of employability among engineering students in Nigerian Polytechnics and finally sorts to find out the strength of predictors by investigating the moderating effect of work experience on the relationship between the predictors of employability among engineering students in the Nigerian Polytechnics. Data were obtained from 465 polytechnic engineering students in Nigeria using a simple random sampling to select 5 polytechnics from the north central geopolitical zone and cluster sampling approach to select the 465 students used for the study. The data were analyzed statistically using descriptive and inferential analysis (factor analysis and structural equation modelling). The results of the study revealed that Basic job performance skills, Self-efficacy and Subject understanding had significant effect on employability. Subject understanding having the highest significant effect on employability thus, the most significant predictor of employability followed by basic job performance skills. The last predictor of employability from the study is selfefficacy. The study reveal that five dimensions of basic job performance skills emerged. The most important dimension in basic job performance skills is foundation skills subscale and competency (system technology) followed by competency skillmanagement, basic skill, and thinking skill. Five dimensions of self-efficacy also emerged in the study. The most important dimension of self-efficacy is goal selection and planning followed by problem solving, self-appraisal, and occupational information. Furthermore, six dimensions of subject understanding emerged in this study, the most important dimension in subject understanding is application and practice, followed by system approach, engineering discipline, science and practice, professionalism, and problem solving. Finally, three dimensions of employability emerged in this study. The most important dimension for employability is marketability, followed by job retention, and lastly job seeking duration. The research findings further revealed the moderating effect of work experience on the relationship between the IVs and the DV. The results shows that low and high work experience had a positive significant effect on employability except for self-efficacy which had a positive but no significant effect on employability. The implication is that work experience strengthens basic job performance skills, and selfconfidence of polytechnic students in Nigerian polytechnic giving them a better chance of being employed in the labor market. Based on the findings, it was suggested that authorities in charge of Nigerian education sector should put in place appropriate policy thrust to enhance delivery of quality education that will facilitate acquisition of skills necessary for employment of polytechnic engineering graduates. Curriculum development in line with the global best practice, including training of academic staffs that could ensure the acquisition of basic job performance skills, subject understanding and self-efficacy of polytechnic engineering students should be put in place.